Knowledge discovery, knowledge engineering and knowledge management : 4th international joint conference, IC3K 2012, Barcelona, Spain, October 4-7, 2012, Revised Selected Papers - Dietz, Jan L. G.; Liu, Kecheng; Filipe, Joaquim (Communications in Computer and Information Science, 2013)
This book constitutes the thoroughly refereed proceedings of the 4th International Joint Conference on Knowledge Discovery, Knowledge Engineering and Knowledge Management, IC3K, held in Barcelona, Spain, in October 2012. The 29 best papers were carefully reviewed and selected from 347 submissions. The papers are organized in topical sections on knowledge discovery and information retrieval; knowledge engineering and ontology development; knowledge management and information sharing.